THE NECESSITY OF LEARNING ENGLISH FOR TECHNICAL COLLEGE STUDENTS - NEMATOV DAVLATBEK, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract In  the  twenty-first  century,  English  has  become  the  dominant  language  of science,  technology,  business,  and  international  communication.  For  students  of technical colleges, proficiency in English is not simply an academic requirement but a professional  necessity.  A  large  proportion  of  scientific  publications,  technical documentation,  international  standards,  and  digital  learning  platforms  operate  in English.  As  a  result,  students  who lack English  skills  face  limitations in accessing updated  knowledge,  participating  in  research,  and  competing  in  the  global  labor market. This  paper  analyzes  the  necessity  of  learning  English  for  technical  college students. It explores the academic, professional, and social importance of English in technical  education.  The  article  also  discusses  how  English  proficiency  enhances employability, supports international  cooperation, and encourages lifelong learning. The  study  concludes  that  English  should  be  treated  as  an  essential  component  of technical training programs.